Adrenocortical carcinoma (ACC): diagnosis, prognosis, and treatment - Libé, Rossella (Frontiers in Cell and Developmental Biology, 2015)
Adrenocortical carticnoma (ACC) is a rare malignancy with an incidence of 0.7–2.0 cases/million habitants/year. The diagnosis of malignancy relies on careful investigations of clinical, biological and imaging features before surgery and pathological examination after tumor removal. Most patients present with steroid hormone excess or abdominal mass effects, but 15% of patients with ACC is initially diagnosed incidentally. After the diagnosis, in order to assess the ACC prognosis and establish an adequate basis for treatment decisions different tools are proposed. The stage classification pro¬posed by the European Network for the Study of Adrenal Tumors (ENSAT) is recommended. Pathology reports define the Weiss score, the resection status and the proliferative index, including the mitotic count and the Ki67 index. As far as the treatment is concerned, in case of tumor limited to the adrenal gland, the complete resection of the tumor is the first option. Most patients benefit from adjuvant mitotane treatment. In metastatic disease, mitotane is the cornerstone of initial treatment, and cytotoxic drugs should be added in case of progression. Recently, the First International Randomised (FIRM-ACT) Trial in metastatic ACC reported the association between mitotane and etoposide/ doxorubicin/cisplatin (EDP) as the new standard in first line treatment of ACC. In last years, new targeted therapies, including the IGF 1 receptor inhibitors, have been investigated, but their efficacy remains limited. Thus, new treatment concepts are urgently needed. The ongoing "omic approaches" and next-generation sequencing will improve our understanding of the pathogenesis and hopefully will lead to better therapies.